Chronic thromboembolic pulmonary hypertension and left ventricular filling pressures. (3rd October 2022) - Gerges, C; Pistritto, A M; Gerges, M; Friewald, R; Hofbauer, T; Hartig, V; Dannenberg, V; Skoro-Sajer, N; Moser, B; Taghavi, S; Klepetko, W; Lang, I M
Abstract: Background: Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by chronic obstruction of major pulmonary arteries with organized thrombi and is classified as pre-capillary pulmonary hypertension (PH) by the current hemodynamic definition of the guidelines. However, clinical risk factors for PH due to left heart disease including features of the metabolic syndrome, left-sided valvular heart disease and stable ischemic heart disease can be frequently observed in patients with CTEPH. The aim of this study was to investigate the prevalence, mechanisms and prognostic implications of elevated left ventricular filling pressures (LVFP) in patients with CTEPH. Methods: 394 consecutive CTEPH patients undergoing a first diagnostic right and left heart catheterization were included in this study. mPAWP and LVEDP were utilized for assessment of LVFP. Two cutoffs were applied to identify patients with elevated LVFP: (1) mPAWP and/or LVEDP >15 mmHg as recommended by the current PH guidelines and (2) mPAWP and/or LVEDP >11 mmHg, which is the upper limit of normal in healthy subjects. Clinical and echocardiographic features as well as long-term mortality data were assessed. Results: LVFP was >15 mmHg in 41 (10.4%) and >11 mmHg in 155 patients (39.3%). Univariable logistic regression analysis identified age, body mass index, systemic hypertension, diabetes, atrial fibrillation, mitral regurgitation and left atrial volume as significant clinical predictors of elevated LVFP. Systemic hypertension, atrial fibrillation, mitral regurgitation and left atrial volume remained independent determinants of LVFP in adjusted analysis. LVFP >11 mmHg was associated with worse long-term survival (p-logrank = 0.020). Conclusions: Elevated LVFP is common in patients with CTEPH at the time of diagnosis. Elevated LVFP in CTEPH appears to be due to comorbid left heart disease. CTEPH patients with LVFP >11 mmHg have worse outcomes. Funding Acknowledgement: Type of funding sources: None.